Daya dukung kualitas air harian untuk pertumbuhan ikan nila (Oreochromis niloticus) dalam kolam budidaya di Balai Benih Ikan Lokal (BBIL) Koya Barat Distrik Muara Tami Kota Jayapura - Mantayborbir, Vyona; Indriyani, Ervina; Bukit, Elysabeth Anggreini (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2023)
This research aims to determine the daily carrying capacity of water quality in tilapia cultivation ponds at the West Koya Local Fish Seed Center (BBIL), Muara Tami District, Jayapura City. This research used two earthen ponds measuring 25 x 50 m, water depth 30-50 cm, water volume 100 L in one pond. Tilapia fish (Oreochromis niloticus) with an average length of 20 cm and weight of 243 grams were used in this study. Feed at a rate of 3% of fish biomass is given three times a day. The water quality parameters observed in this study were water temperature measured using a digital thermometer, dissolved oxygen using a DO meter DO 30N, water acidity using a pH meter, pH-240L, SERA aqua-test kit used to measure ammonia and nitrate. This research shows that the water quality parameters observed are normal according to the needs of tilapia fish. So it can be concluded that the water quality in the tilapia cultivation ponds at the West Koya Local Fish Seed Center (BBIL), Muara Tami District, Jayapura City is controlled and suitable for the growth and survival of the cultivated tilapia (Oreochromis niloticus).